Speaking the truth in love : theological and spiritual exhortations of Ecumenical Patriarch Bartholomew - Bartholomew I, Ecumenical Patriarch of Constantinople, 1940- (Orthodox Christianity and contemporary thought., 2010)
A collection of the writings & statements of His All Holiness Ecumenical Patriarch Bartholomew, which challenges the taboos & controversies swirling within religious doctrine, addressing issues such as church unity, papal primacy & divisions within Christianity.